VISUAL OUTCOME AND SELF-SATISFACTION AFTER CATARACT SURGERY IN PATIENTS ATTENDING SHAHEED DR. ASO HOSPITAL, SULAIMANIYAH CITY, IRAQ - Hamasalh, Bakhtiar Qadir (Journal of Sulaimani Medical College, 2022)
Background Cataract is a natural lens opacification and the leading cause of reversible blindness. Globally, it causes 50- 90% of all blindness in developing countries. However, there are no available methods to prevent or treat cataracts rather than surgery; thus, greater attention is needed to guarantee the adequate performance of the surgery. Objectives To detect the cataract surgery visual outcome and the patient’s satisfaction in Sulaimaniyah city, regardless of induced changes in corneal curvatures, size of the pupil, depth of the anterior chamber, and intraocular lens properties. Patients and Methods This cross-sectional study was conducted on 160 patients who attended Shaheed Dr. Aso hospital after cataract surgery. We interviewed the patients and obtained their clinical information at least three months postoperatively. Patient satisfaction was measured as unfair, fair, reasonable, and sound. In addition, with clinical data from our questionnaire, we assessed factors associated with poor outcomes. Then, visual acuity (VA) was measured and announced as borderline, exemplary, or excellent. Results The mean age of participants who underwent cataract surgery was 63.74±11.2 years, of which 63.7% were female. We found that the postoperative mean VA gradually decreased with age. We also compared the obtained data with vision satisfaction. Consequently, we found that patient satisfaction was significantly correlated with the visual outcome. Conclusion The visual outcome was excellent in younger patients, those done in private sectors, and patients with no ocular comorbidities. Patient satisfaction was strongly related to their graphic work.
Keywords: Cataract; Phacoemulsification; Visual outcome; Patient satisfaction